The potential and limits of farmers’ groups as catalysts of women leaders - Nakazi, Florence; Aseete, Paul; Katungi, Enid M.; Ugen, Michael Adrogu (Informa UK Limited, 2017)
The Women’s Empowerment in Agriculture Index revealed weak leadership and influence of women in the community as indicators of women’s political disempowerment. Collective action through farmer groups can be an important strategy for women members to strengthen their political power. The study horns in to analyze the potential group characteristics that can act as catalysts to the number of leadership positions that women occupy. The study uses data from 65 farmers’ groups in central Uganda. Tobit regression model was used to assess the group factors that influence the proportion of positions women held in groups. The study found that groups had an average of 5 leadership positions and women strong leadership skills lie in being treasurers (70%). Number of households represented (10.7%), record keeping (27.9%), proportion of both youth (19.4%), and women (69.7%), number of economic activities (2.9%) were the key factors that influence the proportion of women in group leadership. The findings are useful in guiding development interventions that use group-based approaches in agricultural production and marketing.